Exploring the Skin Mycobiome in Very Preterm babies during the early neonatal period in a Neonatal Intensive Care Unit of India. (April 2022) - Shah, Pritik A; Govindarajan, Varun; Diggikar, Shivshankar; Rangaiah, Ambica; Devadas, Sahana; Kariyappa, Mallesh
The neonatal skin microbiome consists of all the genomes and genetic products of micro-organisms harbouring the skin of babies. Host and the microbiota develop a harmonious environment resulting in symbiosis. Any disruption of this environment could lead to pathological disease. Our study was conducted to explore the neonatal skin fungal microbiome of very preterm neonates admitted to Neonatal Intensive Care Unit at a tertiary health care setting using Next Generation Sequencing of the18S rRNA gene. The most abundant genera found in 22/30 samples were Candida followed by Bipolaris & Cladosporium on the skin microbiome of these neonates. The presence of these fungi, whether just as commensals or as potential pathogens, is currently under research, owing to the risk of early exposure and incidence of infection right from birth.